Comparison of nerve conduction velocities of lower extremities between runners and controls - Colak, T.; Bamac, B.; Gönener, A.; Özbek, A.; Budak, F. (Journal of Science and Medicine in Sport, 2005)
Peripheral nerve injuries can occur in runners, but large numbers of nerve injuries remain subclinical. Identification of nerve injuries needs an understanding of common sites of entrapment in running. Fourteen asymptomatic male middle-distance runners and 14 non-active subjects participated in this study. The neurophysiologic study consisted of motor and sensory nerve conduction of medial and lateral plantar nerves, sensory nerve conduction of sural and superficial peroneal nerves, and motor nerve conduction of common peroneal nerve. Active range of motion and muscle strength assessment (dorsi flexion/plantar flexion; inversion/eversion) as measured using a Biodex System3 Dynamometer were observed to be within normal limits for both groups. The medial plantar (sensory) nerve and sural nerve distal latencies were significantly prolonged and sensory conduction velocities were significantly delayed in the runners compared with the control subjects. Many of the asymptomatic runners with abnormal nerve conduction tests in this study may represent presymptomatic or asymptomatic neuropathy similar to the type of subclinical entrapment neuropathy.